2017
DOI: 10.3390/recycling2030011
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions and Practices of Solid Waste Recycling in the City of Laramie in Wyoming, U.S.A.

Abstract: Managing household solid waste is a growing challenge for many cities. To tackle this problem, cities are turning to recycling, which is an effective tool for solid waste management. This research seeks to understand the public perceptions and practices of recycling in the City of Laramie, Wyoming. Recycling in Laramie began in 1983 with the establishment of the Ark Recycling Center. Laramie officially started its curbside recycling services in September 2011, and in April 2012 the city declared its long-term … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…These scholars claimed to have found a high measurement of consumers attitude to preserve the environment, while in fact they measured consumer attitude towards recycling. When adopting a consumer perspective, previous research described recycling as a method of separating and collecting used or waste products (Bom et al, 2017). Reflecting on the statement of Minton and Rose (1997), in combination with the found consumer definition of recycling, it can be concluded that consumer attitude towards the collection and separation of waste products, and not towards the preservation of the environment, is high.…”
Section: Evaluation Of the Enrichment Of The Tpbmentioning
confidence: 99%
“…These scholars claimed to have found a high measurement of consumers attitude to preserve the environment, while in fact they measured consumer attitude towards recycling. When adopting a consumer perspective, previous research described recycling as a method of separating and collecting used or waste products (Bom et al, 2017). Reflecting on the statement of Minton and Rose (1997), in combination with the found consumer definition of recycling, it can be concluded that consumer attitude towards the collection and separation of waste products, and not towards the preservation of the environment, is high.…”
Section: Evaluation Of the Enrichment Of The Tpbmentioning
confidence: 99%
“…Convenience is a key controlling factor for the willingness to separate waste into recyclable fractions [25,30]. The relative success of kerbside collection probably lies in the availability that comes with the short distances.…”
Section: Type Of Change/comparison and In What Countrymentioning
confidence: 99%
“…Previous studies [3], [12], [14], [15] have shown that such motivations are associated with the amount of information that an individual has about recycling [16], with the degree of routinization, i.e. to what extent recycling is embedded in people's lives [17], [18], and with individual responsibility for the environment [19]. Therefore, the construct is based on three following variables.…”
Section: Responsiveness To Indirect Measuresmentioning
confidence: 99%